Norovirus GII-4 2006b variant circulating in patients with acute gastroenteritis in thailand during a 2006-2007 study - Kittigul,L. (Wiley-Liss Inc., 2015)
Noroviruses (NoVs) are recognized as a significant cause of acute gastroenteritis in children and adults. A 14-month study, from January 2006 to February 2007, was undertaken in a hospital in Thailand to determine the prevalence and genetic characterization of NoVs in patients of all ages with acute gastroenteritis. Based on reverse transcription-nested polymerase chain reaction (RT-nested PCR), NoVs were detected in 122 of 273 (44.7%) collected stool samples. Of the 122 NoV-positive samples, 28 (23%) belonged to GI, 79 (64.8%) belonged to GII, and 15 (12.2%) were mixed infections of GI and GII strains. Three NoV GI-positive and 42 NoV GII-positive samples were characterized successfully by DNA sequencing of the RT-nested PCR products and phylogenetic analysis. For NoV GI, two genotypes were identified: GI-2 (one sample) and GI-6 (two samples). NoV GII could be classified further into five distinct genotypes: GII-2 (1 sample), GII-3 (3 samples), GII-4 (14 samples), GII-6 (3 samples), and GII-17 (2 samples), and one unclassified genotype (19 samples). All NoV GII-4 strains showed 88-98% nucleotide identity with NoV GII-4 2006b variants reported worldwide. Among genotypes of NoV characterized, one co-infected stool sample exhibited NoVs GI-6 and GII-4 2006b. This study suggests that there is an important role of NoVs as etiologic agents in patients with acute gastroenteritis. The predominant circulating genotype of NoV infections is GII-4 2006b variant. © 2010 Wiley-Liss, Inc.